Evapotranspiration and crop coefficients of Moringa oleifera under semi-arid conditions in Pernambuco - Célia S. dos Santos; Abelardo A. de A. Montenegro; Márcio A. L. dos Santos; Elvira M. R. Pedrosa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Efficient water use in agriculture is fundamental, especially in semi-arid regions where water scarcity is intense. The aim of this study was to estimate water requirements and crop coefficients in the different phenological stages of Moringa oleifera. The experiment was carried out from February to April 2015 at the Experimental Unit for Reuse and Hydrological Management, located in Mutuca, PE (7º 15’ 18’’ S, 35º 52’’ 40’’ W, 550 m). A lysimeter was used to estimate crop evapotranspiration. Reference evapotranspiration (ETo) was estimated by indirect methods. In the lysimeter, soil salinity and leaf water potential of the crop were monitored. The direct and indirect methods presented an excellent performance compared with the standard grass-lysimeter, especially Hargreaves-Samani, which presented a remarkable result for the study area. Crop coefficients (Kc) ranged from 0.73 to 1.73 in the different phenological stages. Moringa crop evapotranspiration (ETc) exhibited temporal variations, with a cumulative rate of 139.8 mm, for a cumulative reference evapotranspiration of 130.97 mm. Moringa plants showed slight water restriction, at the times of lower solar radiation.